Monkey gaze behaviour during action observation and its relationship to mirror neuron activity. Issue 12 (9th October 2013) - Maranesi, Monica; Ugolotti Serventi, Francesca; Bruni, Stefania; Bimbi, Marco; Fogassi, Leonardo; Bonini, Luca
Abstract Mirror neurons (MNs) of the monkey ventral premotor cortex (area F5) are a class of cells that match the visual descriptions of others' actions with correspondent motor representations in the observer's brain. Several human studies suggest that one's own motor representations activated during action observation play a role in directing proactive eye movements to the site of the upcoming hand–target interaction. However, there are no data on the possible relationship between gaze behaviour and MN activity. Here we addressed this issue by simultaneously recording eye position and F5 MN activity in two macaques during free observation of a grasping action. More than half of the recorded neurons discharged stronger when the monkey looked at the action than when it did not look at it, but their firing rate was better predicted by 'when' rather than by 'how long' the monkey gazed at the location of the upcoming hand–target interaction. Interestingly, the onset of MN response was linked to the onset of the experimenter's movement, thus making motor representations potentially exploitable to drive eye movements. Furthermore, MNs discharged stronger and earlier when the gaze was 'proactive' compared with 'reactive', indicating that gaze behaviour influences MN activity. We propose that feedforward, automatic representations of other's actions could lead eye movements that, in turn, would provide the motor system with feedback information that enhances the neural representations of the ongoing action.